Myocardial revascularization strategies in diabetic patients with multi-vessel disease: CABG vs DES-based PCI. - Kassimis, G; Patel, N; Banning, A (Bentham Science Publishers B.V., 2014)
Randomized trials comparing multi-vessel percutaneous coronary intervention to coronary artery bypass grafting (CABG) have demonstrated the long-term superiority of CABG in diabetic patients. Benefits include improved survival, fewer recurrent myocardial infarctions and a lower risk of the need for repeat intervention. The focus of this review article is to review the contemporary management of diabetic patients with multi-vessel coronary artery disease.